Caracterização físico química, perfil sensorial e aceitação de morangos submetidos à irradiação - Scolforo, Carmelita Zacchi (2014)
Irradiation is a non-thermal preservation method used in different foods and at different dosages. Changes in the physico-chemical characteristics and in food quality depend on the applied dosage of radiation. Therefore, the aim of this study was to analyze the effect of radiation in the physico-chemical characteristics of irradiated strawberries. The irradiation of the samples was taken one day after harvest and was performed at the Laboratory of Gama Radiation of the Development Center of Nuclear Technology (CDTN) in Belo Horizonte-MG. The radiation doses used were 1 kGy, 2 kGy, 3 kGy and 4 kGy and the control sample (0 kGy). We evaluated the pH, titratable acidity (ATT), soluble solids (SS), the ratio (SS/ATT), total sugars, reducing and non-reducing sugars, pectin, ascorbic acid, firmness, color, anthocyanins (by three different methods of analysis), phenolics and antioxidant capacity. For the sensory characterization of the samples, it was used the Optimized Descriptive Profile (PDO). Fifteen selected judges participated of the analyses. The attributes evaluated were characteristic color, sweetness, sour taste, firmness and juiciness. Sensory acceptance was performed with 60 consumers of strawberry in two sessions. Irradiation did not significantly change most of the analyzed characteristics; only the firmness showed statistically different values: by increasing the dose, the firmness of the strawberry decreased. In PDO, the samples differed in color, sweetness, firmness and juiciness, and the control sample and the sample irradiated at 1 kGy had higher values of firmness and lower juiciness and sweetness. Regarding acceptance, the control sample and the sample irradiated at 1 kGy did not differ by Tukey test at 5%, but they differed from samples irradiated at doses of 3 kGy and 4 kGy; the sample with a dose of 2 kGy did not differ from any other sample. In this study we tested correlations between pH, titratable acidity (ATT), soluble solids (SS), total sugars and non-reducing sugars, anthocyanins (pH differential), pectin, instrumental firmness, relation SS/ATT (ratio), the color parameters “a”, “b”, “c” and “L”, and the sensory descriptive data, which were firmness, juiciness, sweetness and sour taste. Significantly positive correlation were found between pH and ratio, SS and pectin, anthocyanins and “a”, “c” values, sugars and “b”, “c” values, sensory firmness and instrumental firmness, juiciness and sweetness, sensory firmness and sour taste. Significantly negative correlation were found between ATT and ratio, SS and instrumental firmness, anthocyanins and “L”, juiciness and instrumental firmness, sensory firmness and sour taste, xviii sensory firmness and sweetness. In this study, we also determined the physico-chemical and sensory characteristics of strawberries irradiated at the DT and CRT dosages, and evaluated the influence of packaging in sensory acceptance of irradiated strawberries at the CRT dosage (3.6 kGy). There was little variation in physico-chemical characteristics between control sample and DT and CRT samples; however the instrumental firmness decreased with the increasing of the dose. The values of the global difference of color, ?E* were above 8.0, therefore, the difference in color between samples are easily noticeable to the human eyes. The values of the attributes sour taste and sweetness were similar between samples, but for firmness, juiciness and color the values varied according to radiation doses. The sensory acceptance of control sample did not statistically differ (p>0.05) from the CRT sample, and the information that the strawberry was irradiated did not affect the sensory acceptance; in other words, the control sample and the CRT sample had good acceptance. It can be concluded that irradiation is a preservation method that can be used in strawberries since it exerts little influence on their physico-chemical and sensory characteristics, in the studied period of time.